Motivasi Audiens terhadap Kecenderungan Menonton Channel YouTube Windah Basudara - Rifqi Khaerul Rahman; Kurnia (Bandung Conference Series: Journalism, 2023)
Abstract. YouTube is one of the Social Broadcasting Networks media whose usage in Indonesia is increasing to 80.57 million and is projected to continue to increase to 96.80 million users in 2025. This study aims to determine the factors that motivate the use of YouTube and its influence on the tendency to watch Windah Basudara's YouTube content. This type of quantitative approach became the method in this study, using purposive sampling as the sampling technique. Windah Basudara YouTube channel subscribers became the population in this study, by setting the sampling criteria Windah Basudara YouTube channel subscribers, Windah Basudara YouTube channel viewers, and owning a personal YouTube channel or account. A total of 100 respondents were determined as a representative sample. Research data was collected through online surveys and analyzed using Partial Least Square (PLS). The results showed that entertainment, habit, escape, and communication variables proved to have a positive effect on YouTube viewing so that the research hypothesis was accepted or supported. Based on these findings, the communication variable is considered the most dominant in order to have a positive effect on increasing the intensity of the audience. Therefore, to increase audience intensity, Windah Basudara must be able to ensure that the broadcast content is able to make its subscribers express their opinions about gaming in the comments column, and must be encouraged to continue being active. Subscribers' opinions about gaming in the comments column can also be used as an illustration to see interest and need for reviews related to gaming. Abstrak. YouTube merupakan salah satu media Social Broadcasting Networks yang di Indonesia penggunaannya semakin meningkat hingga 80,57 juta dan diproyeksikan terus meningkat hingga 96,80 juta pengguna di tahun 2025. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang menjadi motif penggunaan YouTube dan pengaruhnya terhadap kecenderungan menonton konten YouTube Windah Basudara. Jenis pendekatan kuantitatif menjadi metode dalam penelitian ini, menggunakan purposive sampling sebagai teknik pengambilan sampelnya. Subscriber channel YouTube Windah Basudara menjadi populasi pada penelitian ini, dengan menetapkan kriteria sampling subscriber channel YouTube Windah Basudara, penonton channel YouTube Windah Basudara, serta memiliki channel atau akun YouTube pribadi. Sebanyak 100 responden ditetapkan sebagai sampel yang mewakili. Data penelitian dikumpulkan melalui survey online dan dianalisis menggunakan Partial Least Square (PLS). Hasil penelitian menunjukan bahwa variabel entertainment, habit, escape, dan communication terbukti berpengaruh positif terhadap YouTube viewing sehingga hipotesis penelitian diterima atau didukung. Berdasarkan temuan tersebut, maka variabel communication dinilai paling dominan untuk dapat memberikan efek yang positif untuk meningkatkan intensitas penonton. Oleh karena itu, untuk meningkatkan intensitas penonton, Windah Basudara harus dapat memastikan bahwa konten tayangannya mampu membuat subscribe nya menyampaikan pendapat mereka tentang gaming di kolom komentar, dan harus didorong agar terus aktif. Pendapat subscriber tentang gaming di dalam kolom komentar juga dapat dijadikan gambaran untuk melihat ketertarikan dan kebutuhan review terkait gaming.